THE EFFECT OF THE EFFICIENCY OF INVESTMENT DECISIONS ON THE FIRM VALUE A SAMPLE OF IRAQI COMPANIES LISTED ON THE IRAQI STOCK EXCHANGE (World Bulletin of Management and Law, 2022)
The research aims to measure the effect of free cash flow on the efficiency of investment decisions and their reflection on the value of the firm. The free and efficient investment decisions in the value of the firm, based on the data of the annual financial reports for a sample of the Iraqi companies listed in the Iraqi Stock Exchange, which numbered (27) companies, represented by (15) companies from the banking sector and (8) companies from the industrial sector and (4) A firm from the insurance sector for the period from (2011-2020). For the purpose of measuring the efficiency of investment decisions, a model (Mcnichols & Stubben, 2008) was used, and for the purpose of measuring the value of the firm, it was relied on the (Tobin's Q) model, and for the purpose of statistically testing the research hypotheses, the statistical program (spss) was used to find out the size of the effect among the research variables. The research reached several results, the most important of which is that there is no statistically significant effect of the efficiency of investment decisions on the firm's value.